ANALYSIS OF INDICATORS INDICATING EMPLOYMENT OF THE POPULATION THROUGH SERVICE PROVISION IN RURAL AREAS - Usmonov, Murodbek (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This article systematically analyzes indicators of employment and well-being of the population through the service sector in rural areas. The study examines the development of service sectors, their impact on employment levels and economic activity in the period 2020–2024. According to the results of empirical analysis based on data from the Statistics Agency of the Republic of Uzbekistan, the service sector is an important source of income for the rural population and is a key factor in ensuring infrastructure development and socio-economic stability.